Treatment of Bacterial Vaginosis: A Multicenter, Double-Blind, Double-Dummy, Randomised Phase III Study Comparing Secnidazole and Metronidazole - Bohbot, Jean-Marc (Hindawi Publishing Corporation, 2010)
Objective. Multiple-dose metronidazole oral therapy is currently the reference treatment for bacterial vaginosis (BV). This double-blind, double-dummy, noninferiority study compared the efficacy of secnidazole, another nitroimidazole with pharmacokinetics allowing a single dose regimen, to this standard treatment. Methods. A total of 577 patients were randomized to receive metronidazole (500 mg, b.i.d for seven days) or secnidazole (2 g, once). Therapeutic cure at D28 was defined as the resolution of vaginal discharge, positive KOH whiff test, vaginal pH >4.5 and Nugent score >7 on Gram-stained vaginal fluid. Results. According to this primary endpoint, the single-dose secnidazole regimen was shown to be at least as effective as the multiple-dose metronidazole regimen (60.1 % cured women vs 59.5% , 95% confidence interval with a noninferiority margin of 10%: [−0.082; 0.0094]). Safety profiles were comparable in both groups. Conclusion. The secnidazole regimen studied represents an effective, convenient therapeutic alternative that clinicians should consider in routine practice.